Post-election survey data: Local democracy and the 2018 local elections in the Czech Republic - Šaradín, Pavel; Lebeda, Tomáš; Lysek, Jakub; Soukop, Michal; Ostrá, Daniela; Lebedová, Eva (Data in brief, 2021)
This article presents unique survey data focused on local democracy, political attitudes and political participation. The main aim of the research was to understand the relationships between political values, political participation, political knowledge and voting behavior at the local level. The survey was held at autumn 2018 after local elections in the Czech Republic. The data are unique in terms of their focus on local politics combined with variables that are standardly examined in the context of national politics. The dataset links research fields that are directly related to local politics (local electoral participation, local electoral behavior, local non-electoral participation, trust in local institutions and evaluation of local policy efficacy) with the fields usually connected with national politics (political interest, trust in institutions, political cynicism, populist attitudes and political knowledge). Research also looks at attitudes towards democracy as such. The provided data can be used by scholars in the field of local politics, local governance and electoral behavior. Data are comparable to other large-scale individual level surveys, or may serve as data source for meta-analysis.
Keywords: Attitudinal concepts; Sociology; Social survey data; Local politics